A new amine‒carbonyl fused emitter with hybridized excited state for green OLED with high luminance and low efficiency roll-off. (December 2022) - Qiu, Xu; Li, Tengyue; Liu, Chaoke; Liu, Xinyong; Li, Jingwei; Xue, Shanfeng; Pan, Yuyu
Abstract: In this work, a novel green emitter, namely 16, 16-dimethylbenzo[ a ]quinolino[3, 2, 1- de ]acridin-10(16 H )-one (GACQ), with amine‒carbonyl fused structure has been designed and synthesized. The single-crystal structure analysis confirmed that the fused structure shows non-planar conformation with dihedral angle of 48.97° from the front-view direction. The photophysical and theoretical results confirmed that GACQ exhibited hybridized local and charge-transfer (HLCT) feature with strong green emissions of 513 and 535 nm in solution and film, respectively. The non-doped device based on GACQ achieved high luminance (15810 cd m −2 ) and good efficiency stability with negligible external quantum efficiency (EQE) roll-off. Furthermore, the doped device exhibited high maximum EQE of 4.8% with CIE coordinate of (0.38, 0.58). Graphical abstract: Image 1 Highlights: A novel amine‒carbonyl fused emitter, GACQ, has been successfully constructed. GACQ possesses hybridized local and charge-transfer characteristic. Non-doped device of GACQ exhibited high luminance and negligible EQE roll-off. Doped device based on GACQ achieved maximum EQE of up to 4.8%.